Views on attrition and retention among beginning English as a foreign language (EFL) teachers in Israel and implications for teacher education. (February 2018) - Carmel, Rivi; Badash, Merav
Highlights: Insufficient integration of EFL teacher education providers with schools. EFL teachers feel unprepared for the job. Enthusiasm, high self-esteem and satisfaction are important for ensuring retention. Classroom management issues act as catalyst for either retention or attrition. Support from management is cardinal in the decision to stay or leave teaching.